Nanocomposite thin films and coatings : processing, properties and performance - Zhang, Sam; Ali, Nasar (Imperial College Press, 2007)
Materials development has reached a point where it is difficult for a single material to satisfy the needs of sophisticated applications in the modern world. Nanocomposite films and coatings achieve much more than the simple addition of the constitutents - the law of summation fails to work in the nano-world. This book encompasses three major parts of the development of nanocomposite films and coatings: the first focuses on processing and properties, the second concentrates on mechanical performance, and the third deals with functional performance, including wide application areas ranging fro.